Dual-Layer Spectral CTA for TAVI Planning Using a Split-Phase Protocol and Low-keV Virtual Monoenergetic Images: Improved Image Quality in Comparison with Single-Phase Conventional CTA - Mangold, David; Salatzki, Janek; Riffel, Johannes; Kauczor, Hans-Ulrich; Weber, Tim Frederik (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose Adaptation of computed tomography protocols for transcatheter aortic valve implantation (TAVI) planning is required when a first-generation dual-layer spectral CT scanner (DLCT) is used. The purpose of this study was to evaluate the objective image quality of aortic CT angiography (CTA) for TAVI planning using a split-phase technique with reconstruction of 40 keV virtual monoenergetic images (40 keV-VMI) obtained with a DLCT scanner. CT angiography obtained with a single-phase protocol of a conventional single-detector CT (SLCT) was used for comparison.Materials and Methods 75 CTA scans from DLCT were retrospectively compared to 75 CTA scans from SLCT. For DLCT, spiral CTA without ECG-synchronization was performed immediately after a retrospectively ECG-gated acquisition covering the heart and aortic arch. For SLCT, spiral CTA with retrospective ECG-gating was performed to capture the heart and the access route simultaneously in one scan. Objective image quality was compared at different levels of the arterial access route.Results 40 keV virtual monoenergetic images of DLCT showed a significantly higher mean vessel attenuation, SNR, and CNR at all levels of the arterial access route. With 40 keV-VMI of DLCT, the overall mean aortic attenuation of all six measured regions was 589.6 ± 243 HU compared to 492.7 ± 209 HU of SLCT (p < 0.01). A similar trend could be observed for SNR (23.6 ± 18 vs. 18.6 ± 9; p < 0.01) and CNR (21.1 ± 18 vs. 16.4 ± 8; p < 0.01). No deterioration was observed for vascular noise (27.8 ± 9 HU vs. 28.1 ± 8 HU; p = 0.599).Conclusion Using a DLCT scanner with a split-phase protocol and 40 keV-VMI for TAVI planning, higher objective image quality can be obtained compared to a single-phase protocol of a conventional CT scanner.Key Points: Citation Format
Keywords: transcatheter aortic valve implantation (TAVI); transcatheter aortic valve replacement (TAVR); dual-energy CT; spectral detector CT; aortography; virtual monoenergetic imaging